Social mobility in post-apartheid South Africa - Nzimande, Nqobile (Rhodes University, 2026)
This study presents a comprehensive multi-dimensional analysis of social mobility in post-apartheid South Africa by examining structural, intergenerational, and intragenerational mobility patterns across different demographic groups from 1994 to 2017. Despite extensive policy interventions aimed at addressing historical inequalities, South Africa has remained one of the most unequal societies globally, with a Gini coefficient of 0.69. This research evaluates whether the post-apartheid era has delivered on its promise of increased social mobility and reduced inequality. The study employs two nationally representative datasets: the Post-apartheid Labour Market Series (PALMS) and the National Income Dynamics Study (NIDS). These are analysed through Two-Sample Two-Stage Least Squares (TSTSLS) estimation, inequality of opportunity (IOP) decomposition, and transition matrix analysis. The research examines structural shifts in earnings and access to educational and labour market opportunities, estimates intergenerational earnings elasticity across multiple parent-child gender combinations, and provides evidence of "sticky floor" and "sticky ceiling" effects. The findings reveal complex patterns of progress alongside persistent inequality. Substantial educational progress occurred, particularly for Black Africans whose median years of education increased from 8 to 11 years. However, these gains did not translate proportionally into labour market advancement. Intergenerational mobility remains severely constrained, with IGE estimates of 0.45 to 0.65, placing South Africa among countries with the lowest mobility globally. Racial disparities persist: Black African IGE estimates reach 0.82 compared to 0.19-0.20 for White South Africans. The inequality of opportunity analysis reveals that over one-third of total earnings inequality stems from inherited circumstances, with parental education contributing 34%. Intragenerational analysis demonstrates remarkable persistence, with over 70% remaining in both elementary and professional occupations throughout 2008-2017. These findings demonstrate that apartheid's institutional legacy continues to shape mobility outcomes through distinct mechanisms across racial and gender lines. The research provides insights for targeted policy interventions aimed at addressing persistent inequalities and enhancing social mobility.
a multi-dimensional analysis of structural, intergenerational and intragenerational change
Keywords: Uncatalogued